Integrated PacBio SMRT and Illumina sequencing uncovers transcriptional and physiological responses to drought stress in whole-plant Nitraria tangutorum - Wei, Meiying; Wang, Bo; Li, Chaoqun; Li, Xiaolan; He, Cai; Li, Yi (Frontiers in Genetics, 2024)
Nitraria tangutorum Bobr., a prominent xerophytic shrub, exhibits remarkable adaptability to harsh environment and plays a significant part in preventing desertification in northwest China owing to its exceptional drought and salinity tolerance. To investigate the drought-resistant mechanism underlying N. tangutorum, we treated 8-week-old seedlings with polyethylene glycol (PEG)-6000 (20%, m/m) to induce drought stress. 27 samples from different tissues (leaves, roots and stems) of N. tangutorum at 0h, 6h and 24h after drought stress treatment were sequenced using PacBio single-molecule real-time (SMRT) sequencing and Illumina RNA sequencing to obtain a comprehensive transcriptome. The PacBio SMRT sequencing generated 44,829 non-redundant transcripts and provided valuable reference gene information. In leaves, roots and stems, we identified 1162, 2024 and 232 differentially expressed genes (DEGs), respectively. The Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that plant signaling and mitogen-activated protein kinase (MAPK) cascade played a pivotal role in transmitting stress signals throughout the whole N. tangutorum plant following drought stress. The interconversion of starch and sucrose, as well as the biosynthesis of amino acid and lignin, may represent adaptive strategies employed by N. tangutorum to effectively cope with drought. Transcription factor analysis showed that AP2/ERF-ERF, WRKY, bHLH, NAC and MYB families were mainly involved in the regulation of drought response genes. Furthermore, eight physiological indexes, including content of proline, hydrogen peroxide (H2O2), malondialdehyde (MDA), total amino acid and soluble sugar, and activities of three antioxidant enzymes were all investigate after PEG treatment, elucidating the drought tolerance mechanism from physiological perspective. The weighted gene coexpression network analysis (WGCNA) identified several hub genes serve as key regulator in response to drought through hormone participation, ROS cleavage, glycolysis, TF regulation in N. tangutorum. These findings enlarge genomic resources and facilitate research in the discovery of novel genes research in N. tangutorum, thereby establishing a foundation for investigating the drought resistance mechanism of xerophyte.